Corruption in infrastructure procurement : addressing the dynamic criticalities - Owusu, Emmanuel Kingsford; Chan, Albert P. C. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The book conducts a comprehensive examination of the various determining factors of corruption that negatively affect the procurement process and, in the end, result in cost and time overruns. The authors present an in-depth understanding of how the identified determining factors of corruption can be addressed. This book is essential reading for academics, researchers, professionals and stakeholders in the procurement of infrastructure projects and civil works, and those with an interest in corruption, construction management and construction project management"--
Introduction: Let's talk about corruption again -- Contemporary overview of corruption in infrastructure procurement process : past to present -- Forms of corruption : a longitudinal review and empirical assessment of the multiple facets of corruption in infrastructure projects -- A global perspective on the causal factors of corruption in the procurement process of infrastructure related works -- Soft computing assessment of procurement irregularities in the supply-chain of infrastructure project procurement -- Towards a project transparency performance indicator : assessing the potency of anti-corruption measures (ACM) in public infrastructure-related projects from a global perspective -- Barriers against and affecting the application of anti-corruption measures in infrastructure projects : the disparities between developed and developing countries -- Towards a cleaner project procurement : evaluation of construction projects' vulnerability introduction in infrastructure projects -- A turn from discrete to dynamics : developing a dynamic net-framework for extirpating corruption in the infrastructure procurement process -- Introduction to the future : the future is here, and the future is now.
OCLC-licensed vendor bibliographic record.
Keywords: Government purchasing -- Corrupt practices; Public works -- Corrupt practices; Political corruption -- Prevention; ARCHITECTURE / Professional Practice; ARCHITECTURE / Project Management; BUSINESS & ECONOMICS / Business Ethics